Analysis of the Fama-French Three-Factor Model on Stock Returns in LQ45 During 2020-2024 and the Moderating Role of Good Corporate Governance (GCG) - Auro Rahman; Etty Gurendrawati; Ayatulloh Michael Musyaffi (CV. Proaksara Global Transeduka, 2025)
Indonesian stock investment has attracted growing public attention in recent years, though returns remain acutely susceptible to instability driven by conditions like the pandemic, economic revival, and global uncertainties, which reinforces the necessity of identifying the risk factors that shape return patterns. This study evaluates the roles of Market Risk Premium, Small Minus Big, and High Minus Low within the Fama-French Three-Factor model as they pertain to returns for LQ-45 stocks listed on the Indonesia Stock Exchange across the 2020–2024 period, while additionally scrutinising Good Corporate Governance as a moderating variable. Employing a quantitative causal approach, this research draws on secondary data sourced from financial reports, equity prices, and other records. The population encompasses all LQ-45 firms, with a purposive sampling method applied to satisfy predetermined criteria. Data handling includes descriptive statistics, selection tests for panel data regression, classical assumption checks, and application of the Random Effect Model. Findings indicate that MRP and HML produce significant effects on stock returns, but SMB does not. GCG exerts a significant influence as well and moderates the relationships of MRP, SMB, and HML with returns, suggesting that superior governance reinforces the connection between Fama-French factors and performance outcomes. This work contributes to asset pricing discourse within developing economies and offers practical guidance for investors, management, and policymakers in formulating investment and governance strategies.